) Jurisprudence and fundamentalism of the talk (selling the option unless they disperse) - Manal Abdullah Saad Alsafi (Miasto Przyszłości, 2023)
This research dealt with the jurisprudence and fundamentalism of the Hadith: (selling the option unless they differ), the novels of the talk were collected and three fundamentalist rules were inferred: "The origin in all contracts is justice", "The origin in the contracts is the consent of the contractors", and "The rights of the slaves fall with the permission of the slaves". Four jurisprudence rules are: "The Council option rule", "The origin in the sale is the obligation and the failure to commit is due to the casual and the choice", "The lesser arrows" and "The fallen does not return". It appeared that the conversation had to do with three of the five great jurisprudence rules: the rule: "Things by their purposes", the rule of "Damage is still" and the rule of "Habit is a court